Solid Waste Co-Conversion by Hydrothermal Treatment using Natural Zeolite - Maleiva, Lalak Tarbiyatun Nasyin; Wahyu Purnomo, Chandra (Makara Journal of Science, 2020)
Hydrothermal treatment is a thermal conversion technology for processing high-moisture-content solid waste to coal-like materials. In this research, mixtures of sawdust and polyethylene terephthalate (PET) waste were treated in a 2000 mL hydrothermal reactor to produce hydrochar and a liquid product. The effects of zeolite addition and temperature variations during the treatment on the product characteristics were investigated. During the treatment, the utilized temperatures were 180, 200, and 220 °C, and the zeolite contents in the mixture were 10 and 20 wt%; the temperature and zeolite content were varied, while the other processing parameters were fixed, i.e., a biomass-to-PET ratio of 1:1, solid mixture-to-water ratio of 1:10, and processing time of 30 minutes at the targeted temperature. The product from each hydrothermal condition was characterized in terms of solid yield; liquid pH; chemical characteristics, determined using proximate analysis; and calorific value. The result shows that the addition of zeolite could increase the solid yield, while a higher treatment temperature led to a higher calorific value of the solid product.